Theoretical study about L-arginine complexes formation with thiotriazolin - Kucherenko, L. I.; Hromyleva, O. V.; Mazur, I. A.; Shishkina, S. V.; Кучеренко, Людмила Іванівна; Хромильова, Ольга Володимирівна; Мазур, Іван Антонович (Zaporizhzhya state medical university, 2017)
Brain vascular diseases are one of the leading causes of morbidity, mortality and disability of population in the industrialized countries of the world. An important element of this problem’s solution is the creation of new highly effective and safe drugs, which would lead to mortality reduction, to increase in life expectancy and quality of life. Therefore it is interesting to create a new combined drug based on L-arginine and thiotriazolin. The aim of the study: to consider the possible structure and energy characteristics of complexes formed by L-arginine, 3-methyl-1,2,4-triazolyl-5-thioacetate (MTTA) and morpholine. Calculation method. The initial approximation to the complex geometry was obtained using molecular docking with the help of AutoDock Vina program. The obtained ternary complexes were pre-optimized by semi-empirical PM7 method with modeling the impact of the environment by COSMO method. The calculations were carried out using MOPAC2012 program. Then they were optimized by B97-D3/SVP + COSMO (Water) dispersion-corrected DFT-D with geometrical spreading correction on insufficiency of gCP basis set. A more accurate calculation of the solvation energy was conducted by SMD. The calculations by density functional method were carried out using the ORCA 3.0.3 software. Energy complex formation in solution was calculated as the difference of the Gibbs free energy of the solvated complex and its individual components. Results. Quantum chemical calculations show, that thiotriazolin and L-arginine are able to form ternary complexes, where mole¬cules are linked by multiple hydrogen bonds. The calculation data suggest, that studied complexes are thermodynamically unstable in solution. The energies of them are positive, but rather low despite charge gain of a number of intermolecular hydrogen bonds. Finding. Based on the results of the conducted quantum-chemical study of a three components system (MTTA, morpholine, and L-arginine) it is possible to show the possibility to form ternary complexes with low stability in infinite dilute solutions. It should be noted that two negative charges are always localized in formed complexes on the deprotonated carboxyl groups. The positive charges are located either on the guanidine moiety and the α-amino group of L-arginine, or on the guanidine moiety of L-arginine and protonated molecule of morpholine. It can be expected that the strengthening of intermolecular interactions in the real solutions may result in increased stability of the complexes. Судинні захворювання головного мозку – одна з головних причин захворюваності, смертності та інвалідизації населення промислово розвинених країн світу. Важливий елемент вирішення цієї комплексної проблеми – створення нових високоефективних і безпечних лікарських препаратів, застосування яких призводило б до зниження смертності, поліпшення якості та тривалості життя. Тому викликає інтерес створення нового комбінованого препарату на основі L-аргініну з тіотриазоліном. Мета роботи – розглянути можливу структуру та енергетичні характеристики комплексів, що утворені L-аргініном, 3-метил-1,2,4-триазоліл-5-тіоацетатом (МТТА) та морфоліном. Методика розрахунків. Початкове наближення до геометрії комплексів отримано, використовуючи процедуру молекулярного докінгу за допомогою програми AutoDock Vina. Отримані трикомпонентні комплекси були попередньо оптимізовані напівемпіричним методом PM7 із моделюванням впливу середовища методом COSMO. Розрахунки здійснили за допомогою програми MOPAC2012. Потім комплекси були оптимізовані методом функціонала щільності з емпіричною дисперсійною поправкою B97-D3/SVP + COSMO (Water) із застосуванням геометричної поправки на неповноту базисного набору gCP. Більш точний розрахунок енергії сольватації виконаний методом SMD. Розрахунки методом функціонала щільності проведені за допомогою програми ORCA 3.0.3. Енергія утворення комплексів у розчині розраховувалася як різниця вільних енергій Гіббса сольватованого комплексу та сольватованих окремих його компонент. Результати. Квантово-хімічні розрахунки показують, що тіатріазолін і L-аргінін здатні утворювати трикомпонентні комплекси, молекули в яких пов’язані шляхом множинних водневих зв’язків. Результати розрахунків дають змогу припустити, що вивчені комплекси термодинамічно нестабільні в розчині. Енергії утворення комплексів позитивні, але доволі низькі, незважаючи на зарядове посилення ряду водневих зв’язків. Висновки. Квантово-хімічні дослідження системи, що складається з трьох компонент (МТТА, морфолин і L-аргінін), показали можливість утворення трикомпонентних комплексів із невисокою стабільністю в нескінченно розведених розчинах. Варто відзначити, що в утворених комплексах два негативних заряди завжди локалізовані на депротонованих карбоксильних групах. Позитивні заряди локалізовані або на гуанідиновому фрагменті та α-аминогруппі L-аргініну, або на гуанідиновому фрагменті L-аргініну та протонованій молекулі морфоліну. Можна очікувати, що в реальних розчинах посилення міжмолекулярних взаємодій може призвести до збільшення стабільності комплексів.
Теоретичне дослідження можливості утворення комплексів L-аргініну з тіотриазоліном
Keywords: L-arginine; Thiotriazolin; quantum-chemical calculations; molecular complexes; L-аргінін; Тіотриазолін; квантово-хімічні розрахунки; молекулярні комплекси